THE PORTRAYAL OF CHARACTERS AND EDUCATIONAL VALUES IN “THE LAND OF FIVE TOWERS - Nur 'Amaliah; Rifari Baron (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: The objective of the research is to know: 1) The characters in the novel "The Land of Five Towers" 2) The educational value in the novel "The Land of Five Towers." The data is the novel "The Land of Five Towers" by Ahmad Fuadi. This research is qualitative. The writer analyzes the characters by using Nurgiyantoro's categories of characterization. There are six main characters, and they have about 19 personalities. The dominant is religious as all the characters have this personality. The direct method characterization is about 44%, while the indirect method is about 56%. 2) Besides, the educational value is analyzed by Tirtarahardja and Sulo's definitions of values. The dominant one is a moral value: about 80% and religious value is about 20%. In moral value, the dominant is sincerity (31%), and the dominant one in religious value is faithful to God (40%). The novel has a more powerful portrayal of the character and educational value. Hopefully, by analyzing those, the readers will apply the positive lesson they get from the novel in their life.Keywords: character education; educational value; novel analysis